2002
DOI: 10.2172/796221
|View full text |Cite
|
Sign up to set email alerts
|

Transparency of Magnetized Plasma at Cyclotron Frequency

Abstract: Electromagnetic radiation is strongly absorbed by the magnetized plasma if its frequency equals the cyclotron frequency of plasma electrons. It is demonstrated that absorption can be completely canceled in the presence of a second radiation beam, or even a magnetostatic field of an undulator, resulting in plasma transparency at the cyclotron frequency. This effect is reminiscent of the electromagnetically-induced transparency (EIT) of the three-level atomic systems, except that it occurs in a completely classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(28 reference statements)
1
5
0
Order By: Relevance
“…The similar coherence and interference phenomenon, named as EIT-like effect, has been demonstrated in the classical systems such as plasma [14][15][16], mechanical or electric oscillators [17,18], coupled optical resonators [19][20][21][22][23][24], optical parametric oscillators [25][26][27], optomechanical systems [28][29][30] and even some metamaterial configurations [31][32][33]. Especially, the analog of EIT in coupled optical resonators, also called coupled-resonatorinduced transparency, has made great progress in experiment, which has been reported in the different optical systems, such as compound glass waveguide platform using relatively large resonators [34], fiber ring resonators [35], coupled fused-silica microspheres [36,37], integrated micron-size silicon optical resonator systems [38][39][40][41], photonic crystal cavities [42] and graphene-ring resonators [43].…”
supporting
confidence: 56%
“…The similar coherence and interference phenomenon, named as EIT-like effect, has been demonstrated in the classical systems such as plasma [14][15][16], mechanical or electric oscillators [17,18], coupled optical resonators [19][20][21][22][23][24], optical parametric oscillators [25][26][27], optomechanical systems [28][29][30] and even some metamaterial configurations [31][32][33]. Especially, the analog of EIT in coupled optical resonators, also called coupled-resonatorinduced transparency, has made great progress in experiment, which has been reported in the different optical systems, such as compound glass waveguide platform using relatively large resonators [34], fiber ring resonators [35], coupled fused-silica microspheres [36,37], integrated micron-size silicon optical resonator systems [38][39][40][41], photonic crystal cavities [42] and graphene-ring resonators [43].…”
supporting
confidence: 56%
“…1]. Previously, the FEL oscillator start-up from noise has been analyzed in some detail by [16,17], while less complicated analytic expressions for the initial value problem were derived in Ref. [18] for an ideal (no energy spread, constant in time) electron beam in a Fabry-Perottype resonator.…”
Section: B Initial Seeding From Noisementioning
confidence: 99%
“…A critical aspect of induced transparency in plasma is that the electron perpendicular motion due to the probe electric field is canceled by the response to the upper sideband (which is at the probe frequency). Details of mathematical expansion can be found elsewhere [2,3], where it is shown that phase of the sideband field is automatically matched to cancel the probe field.…”
Section: Theory and Simulationmentioning
confidence: 99%
“…A discussion of the polarization of the electron motion can be found in Ref. [3]. The eikonal term was approximated as e ik 1…”
Section: Theory and Simulationmentioning
confidence: 99%
See 1 more Smart Citation